2006
DOI: 10.1111/j.1745-4603.2006.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tuber Density in Potato Sloughing

Abstract: A new CPEM method was developed and used to study the cooking curves of two potato varieties showing differences in texture and of one variety cultivated in four different regimes. The two main cooking curve stages (i.e., cooking and disintegration) can be described by simple linear equations, with density as an independent parameter. The parameters in the equation describing the cooking stage were reformulated to express directly the role of starch. The two new parameters obtained were weakly correlated and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…(a) data see Blahovec and Hejlová (2006); (b) data see Table 3; (c) data see (a) and (b) by mostly lower coefficients of determination R 2 in the case of cv. Saturna in comparison to the other cultivars Agria and Nicola in both years (Tables 3 and data in ).…”
Section: Basic Data Evaluationmentioning
confidence: 99%
“…(a) data see Blahovec and Hejlová (2006); (b) data see Table 3; (c) data see (a) and (b) by mostly lower coefficients of determination R 2 in the case of cv. Saturna in comparison to the other cultivars Agria and Nicola in both years (Tables 3 and data in ).…”
Section: Basic Data Evaluationmentioning
confidence: 99%
“…2000). Similarly, two instrumentally assessed sloughing parameters correlated with specific gravity within varieties, although with significant interactions between varieties (Blahovec and Hejlova 2006). Comparisons between varieties did not support the statement that specific gravity is directly related to mealiness (Mccomber et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, repetitions can be minimized for the characterization of potato lots because of the measurement of a high number of tubers at once. Although mealiness has consistently been associated with high DM content (Burton 1966;Warren and Woodman 1974), their relationship is discussed contradictorily (Linehan and Hughes 1969;Chubey and Mazza 1983;Faulks and Griffiths 1983;Böhler et al 1986;Obeirne and Cassidy 1990;Mccomber et al 1994;Van Marle et al 1997;Thybo et al 2000;Van Dijk et al 2002b;Blahovec and Hejlova 2006;Hejlova et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A range of different methods have been developed for assessing aspects of potato texture 9 including indirect methods, such as the measurement of cell 'sloughing', which assesses the rate of cell separation during cooking. 10 From potato germplasm collections, diploid accessions of Solanum tuberosum group Phureja (Phureja) have been identified which have both distinctive flavour and texture when compared with S. tuberosum group Tuberosum (Tuberosum) types. 11 Cooking time tests revealed appreciable textural differences between Tuberosum and Phureja lines and corresponding microarray studies identified differences in tuber gene expression.…”
Section: Introductionmentioning
confidence: 99%